Effect of colloidal processing on densification and dielectric properties of Ba(Zn1/3Ta2/3)O3 Ceramics. Issue 15 (15th October 2017) - Manivannan, Swathi; Joseph, Andrews; Sharma, P.K.; Raju, K.C. James; Das, Dibakar
Abstract: Colloidal processing of Barium Zinc Tantalate – Ba(Zn1/3 Ta2/3 )O3 (BZT) ceramic and its influences on density, microstructure and microwave dielectric properties have been discussed in this manuscript. Microwave window sections in fusion reactors require dielectric materials with high quality factor and good density. BZT ceramic is one such typical high dielectric material with very high quality factor Q . In this study, processing of BZT powders was carried out using colloidal routes such as, slip-casting and gel-casting and also by conventional die-pressing route. The effects of consolidation technique on densification and microstructure evolution and their subsequent influences on the microwave dielectric properties have been investigated in this work. Linear shrinkage and volume shrinkage of samples remain least for conventional gel casting and maximum for slip casting. Maximum densification with high quality factor (Qxf) of 98, 000 GHz and a high dielectric constant of 29.6 has been achieved for samples processed by conventional gel casting.